Prevalence of Polypharmacy and Factors Affecting Medication Non-Adherence among Non-Communicable Disease Patients in Nakhon Nayok Hospital: An Aspect of General Hospital - Makruasi, Supap; Makruasi, Nisa (Journal of Preventive Medicine Association of Thailand, 2023)
Introduction: Incidence of non-communicable diseases (NCDs) increases in Thailand leading to the use the multidrug agent. The parallel use of multidrug increased the risks of adverse drug reactions. In addition, concomitant administration of multiple drugs may lead to drug adherence and patient compliance. Objectives: This study is aimed to identify the prevalence of polypharmacy and factors related to non-adherence in NCD patients, particularly in a general hospital. Methods: The Cross-sectional analytic study was conducted from August 2019 to December 2019 at the NCDs clinic, Nakhon Nayok hospital. Data included underlying diseases, drug use in the past 6 months, and blood results. All participants have interviewed about the status and reason for non-adherence drugs. Polypharmacy was defined as receiving 5 or more medications while receiving 10 or more medications was defined as extremely polypharmacy. Older patients were defined as aged over 65 years. Results: Of 471 patients included in our study. Female was predominant (308, 65.39%). The mean age of patients was 57 years. Seventeen percent of participants were age older than 65 years. Pre-existing diseases of all patients were hypertension (74.7%), dyslipidemia (65.8%), and diabetic Mellitus (57.5%). Half of the patients were identified as polypharmacy (n= 251). Extremely polypharmacy was found in 20 patients (4.25%). In a subgroup analysis of older patients, there were 51 from 80 adults defined as polypharmacy (63.8%). But extremely polypharmacy was found in 6 of 80 patients (7.5%). Factors related to polypharmacy was diabetic Mellitus (p <0.001), hypertension (p=0.001), dyslipidemia (p=0.003), and high waist circumference (p=0.017), respectively. Conclusions: The high prevalence of polypharmacy was found in our study. Diabetic Mellitus, hypertension, and dyslipidemia were factors associated with polypharmacy.